The Interaction Forces Between Frame and Shear Wall Parts of Optimally Designed Seismic Resistant Highrise Dual System R/C Building - كوكش, أحمد; منير الأطرش; أمجد الحلواني (Latakia University Journal -Engineering Sciences Series, 2024)
Dual systems are of high efficiency in resisting lateral loads under seismic events for high-rise reinforced concrete buildings. As the two parts perform the dual action and both have different deformation modes, the walls are stiffer than the frames and deforms in bending mode, while the frames restrain the shear wall in upper stories because they deform in shear mode. The resulted difference in deformation gives this system the adequate rigidity to resist lateral deformation along the building’s height. But this interaction forces between the two parts might induce an extra demand on the sections of both parts and likewise the cost might rise. This research puts an assumption that as long as the design of the dual system is optimized under a cost objective function, the interaction forces between the two parts would decrease, and this might give several indications and design guides to be fulfilled when designing a dual system. Upon analytically modeling the dual system of this research and performing analysis to optimally design the building of it the results showed that the assumption is correct, and indeed the optimum design of this building gave the lowest interaction forces between the two parts.